2019
DOI: 10.1051/bsgf/2019008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the phase behavior of hydrogen in NaCl brines by molecular simulation for geological applications

Abstract: Hydrogen is targeted to have a significant influence on the energy mix in the upcoming years. Its underground injection is an efficient solution for large-scale and long-term storage. Furthermore, natural hydrogen emissions have been proven in several locations of the world, and the potential underground accumulations constitute exciting carbon-free energy sources. In this context, comprehensive models are necessary to better constrain hydrogen behavior in geological formations. In particular, solubility in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 113 publications
(127 reference statements)
4
26
0
Order By: Relevance
“…The correlation of Torín-Ollarves and Trusler is based on the experimental measurements for NaCl molalities of 0 and 2.5 mol NaCl/kg H 2 O, the experimental data by Wiebe and Gaddy, Wiebe et al, Kling and Maurer, and Choudhary et al for H 2 solubility in pure H 2 O, and the experiments by Crozier and Yamamoto and Gordon et al for solubility of H 2 in saline solutions. Chabab et al provide an extensive experimental data set and a correlation for H 2 solubilities at temperatures of (323 to 373) K, and NaCl molalities in the range of (0 to 5) mol/kg H 2 O. Lopez-Lazaro et al obtained the Henry constants of H 2 in aqueous NaCl solutions for molalities up to 2 mol NaCl/kg H 2 O using excess chemical potentials computed using the WTPI method. ,,, Using the Henry constants reported by Lopez-Lazaro et al, the solubilities of H 2 at a partial pressure of 100 bar are computed and shown in Figures a and b. The simulations of Lopez-Lazaro et al show large error bars (ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of Torín-Ollarves and Trusler is based on the experimental measurements for NaCl molalities of 0 and 2.5 mol NaCl/kg H 2 O, the experimental data by Wiebe and Gaddy, Wiebe et al, Kling and Maurer, and Choudhary et al for H 2 solubility in pure H 2 O, and the experiments by Crozier and Yamamoto and Gordon et al for solubility of H 2 in saline solutions. Chabab et al provide an extensive experimental data set and a correlation for H 2 solubilities at temperatures of (323 to 373) K, and NaCl molalities in the range of (0 to 5) mol/kg H 2 O. Lopez-Lazaro et al obtained the Henry constants of H 2 in aqueous NaCl solutions for molalities up to 2 mol NaCl/kg H 2 O using excess chemical potentials computed using the WTPI method. ,,, Using the Henry constants reported by Lopez-Lazaro et al, the solubilities of H 2 at a partial pressure of 100 bar are computed and shown in Figures a and b. The simulations of Lopez-Lazaro et al show large error bars (ca.…”
Section: Resultsmentioning
confidence: 99%
“…96,97,120,121 Using the Henry constants reported by Lopez-Lazaro et al, 74 the solubilities of H 2 at a partial pressure of 100 bar are computed and shown in Figures 5a and 5b. The simulations of Lopez-Lazaro et al 74 show large error bars (ca. 10−20%).…”
Section: Journal Ofmentioning
confidence: 99%
“…As H 2 solubility and mobility decreases with salinity and lower temperature [ 64 ], an increased influence of seawater intrusions, supported by the mineralogy of these chimneys, may lead to the depleted abundance in hydrogenases observed in OCT and ToMo (Fig. 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Except onshore near the surface above the piezometric level, all sediments are water-saturated however seismic data as experiments show that the gas may invade unconsolidated porous media as soon as the overpressure overpass the effective stress (Fauria and Rempel, 2011). The hydrogen as the methane is poorly soluble in water at low temperature and low pressure (Lopez-Lazaro et al, 2019). Therefore, we simplify the model and consider only the free gas, not the dissolved one.…”
Section: Other Potential Processes That May Influence the H 2 Concentmentioning
confidence: 99%